WOMAN ULAMA'S AUTHORITY ON SOCIAL MEDIA - Badrah Uyuni; Mohammad Adnan (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
This paper discusses woman’s authority in social media, presenting how female scholars appear in social media and convey messages of Islamic teachings. This qualitative study finds that the concept of Maqāṣid sharīʿah was used by them in outlining their da’wah messages. The implication of using this approach leads them to explain religious messages textually and contextually. In practice, they take advantage of the opinions of previous Muslim scholars to support the messages they spread. The presence of women ulama who interact actively through online platforms provides opportunities for Muslim women to choose different information about Islamic teaching in a proportional and personal.